(untitled) (PERcursos Linguísticos, 2023)
ABSTRACT: The research aims to identify idioms composed of zoonymic elements present in the bilingual dictionary entitled “Novo dicionário de expressões idiomáticas americanas”, by Luiz Lugani Gomes. The methodology consists of reading, selecting and digitizing expressions for storage in a database. Idioms are present in the most diverse languages, however, unlike simple words, they are called complex units, as they are formed from the junction of two or more terms whose meaning is generally idiomatic and metaphorical. The problem arises when an individual is faced with these expressions in a written and/or oral dialogue and is not able to understand the meaning due to the semantic non-compositionality of the expression. The justification is in the attempt to help in the understanding of their meanings by contributing to the elaboration of a bilingual glossary of these expressions. Lexicography and Phraseology are taken as a theoretical foundation with authors such asXatara (1998), Biderman (2001), Ortiz Alvarez (2000; 2008), Welker (2004), among others. As a result, a sample of zoonymic idioms in English is offered, with their respective meanings in Portuguese, and a brief analysis in relation to their contexts of use. It concludes by stating that a zoonymic glossary of this nature can contribute to the teaching/learning process of the English language as a support for teachers and learners. Keywords: Phraseology. Lexicography. Zoonymic idioms.